Reputation Engineering in Neurology: Navigating Clinical Authority, Digital Presence, and Content Strategy in the Information Era - Riyanto Sofyan, Henry (Acta Neurologica Indonesia, 2025)
Background: The digital transformation in healthcare has fundamentally altered how neurologists develop and uphold their professional reputation. Although digital professionalism frameworks exist for general medical practice, approaches tailored to neurology remain underdeveloped. Objective: This narrative literature review aims to synthesize evidence exploring the intersection of clinical authority, digital professionalism, and reputation management in neurology and to develop a structured, neurology-specific conceptual framework. Methods: A narrative literature review was conducted by searching PubMed, Scopus, and Google Scholar using terms such as "physician reputation," "digital professionalism neurology," and "online physician reviews,". Studies published from 2008 to 2025 were included if they addressed physician reputation, digital professionalism, online reviews, or health communication strategies relevant to neurological practice. A total of 37 sources were identified and synthesized across eight interconnected themes. Results: This review presents the Neurology Reputation Architecture Model, a three-part framework consisting of Core (clinical competence, ethics, trust), Signal (digital presence, health communication, content strategy), and Shield (risk management, professional boundaries, crisis response). The evidence shows that social media activity, online patient reviews, and digital content strategies significantly influence patient choices, referral patterns, and professional reputation. Neurologists face unique challenges in communicating diagnostic uncertainties and complex neurological concepts in digital settings. Significant gaps remain in neurology-specific empirical research, especially in low- and middle-income countries (LMICs). Conclusion: Effective reputation management in neurology requires blending traditional professionalism with strategic digital engagement. Future research should focus on neurology-specific studies, LMIC contexts, and interdisciplinary methods that combine behavioral science, marketing theory, and sociology of professions.